Feasibility of randomized controlled trials and long-term implementation of interventions: Insights from a qualitative process evaluation of the PEDAL trial - Bulley, Cathy; Koufaki, Pelagia; Macdonald, Jamie Hugo; Macdougall, Iain C.; Mercer, Thomas H.; Scullion, Jane; Greenwood, Sharlene A. (Frontiers in Rehabilitation Sciences, 2023)
Introduction A multi-site randomized controlled trial was carried out between 2015 and 2019 to evaluate the impacts on quality of life of an intradialytic exercise programme for people living with chronic kidney disease. This included a qualitative process evaluation which gave valuable insights in relation to feasibility of the trial and of the intervention in the long-term. These can inform future clinical Trial design and evaluation studies. Methods A constructivist phenomenological approach underpinned face-to-face, semi-structured interviews. Purposive recruitment ensured inclusion of participants in different arms of the PEDAL Trial, providers with different roles and trial team members from seven Renal Units in five study regions. Following ethical review, those willing took part in one interview in the Renal Unit. Audio-recorded interviews were transcribed (intelligent verbatim) and inductively thematically analyzed. Results Participants (n = 65) (Intervention arm: 26% completed; 13% who did not; Usual care arm: 13%; 46% women; 54% men; mean age 60 year) and providers (n = 39) were interviewed (23% PEDAL Trial team members). Three themes emerged: (1) Implementing the Intervention; (2) Implementing the trial; and (3) Engagement of the clinical team. Explanatory theory named “the Ideal Scenario” was developed, illustrating complex interactions between different aspects of intervention and trial implementation with the clinical context. This describes characteristics likely to optimize trial feasibility and intervention sustainability in the long-term. Key aspects of this relate to careful integration of the trial within the clinical context to optimize promotion of the trial in the short-term and engagement and ownership in the long-term. Strong leadership in both the clinical and trial teams is crucial to ensure a proactive and empowering culture. Conclusion Novel explanatory theory is proposed with relevance for Implementation Science. The “Ideal Scenario” is provided to guide trialists in pre-emptive and ongoing risk analysis relating to trial feasibility and long-term intervention implementation. Alternative study designs should be explored to minimize the research-to-practice gap and optimize the likelihood of informative findings and long-term implementation. These might include Realist Randomized Controlled Trials and Hybrid Effectiveness-Implementation studies.